Evaluation of Clinical and Laboratory Characteristics of Cases Diagnosed with Hashimoto’s Thyroiditis - Kurul Demirbaş, Ece; Bezen, Diğdem; Karbuz, Adem (Cerrahpaşa Medical Journal, 2022)
Objective: Hashimoto’s thyroiditis is the most common cause of acquired hypothyroidism and goiter in children and adolescents. The clinical picture can range from euthyroid to overt hypothyroidism or hyperthyroidism. In our study, it was aimed to evaluate the clinical and laboratory data of cases diagnosed with Hashimoto’s thyroiditis. Methods: The data of 113 Hashimoto’s thyroiditis cases who visited the Pediatric Endocrinology outpatient clinic of Health Sciences University Okmeydanı Training and Research Hospital between January 2015 and December 2018 were retrospectively reviewed. Results: Of the 113 cases included in the study, 87 (77%) were girls. The mean age at diagnosis was 12.1 ± 3 years, 70.8% of them were pubertal, 13 of the cases were obese at the time of admission, and 69.9% had a family history of thyroid disease. The 60.2% of the cases were diagnosed with no complaints coincidentally during the examinations performed in primary health care institutions for screening purposes only because they had a family history of thyroid disease. When the presence of additional disease was evaluated, it was observed that 67.2% of them did not have any additional disease and 5.3% had an additional autoimmune disease. At the time of admission, 3 (2.7%) patients were found to have hyperthyroidism, 42 (37.2%) patients were euthyroid, 44 (38.9%) patients had subclinical hypothyroidism, and 24 (21.2%) patients had overt hypothyroidism. While 13.3% were positive for thyroid peroxidase antibody and 10.6% of cases were positive for thyroglobulin antibody, both were positive in 76.1% of cases. Thyroid ultrasonography revealed heterogeneity and pseudonodular structures in the parenchyma of 84.9% of the cases, and heterogeneity and solid nodules in the parenchyma of 10.7%. Conclusion: Hashimoto’s thyroiditis is a common disease in adolescence, especially in girls. In childhood, taking a detailed history at every doctor’s visit, careful evaluation in physical examination and growth and development monitoring, and early recognition of thyroid dysfunctions are important in terms of preventing their negative effects on growth and development. Cite this article as: Kurul Demirbaş E, Bezen D, Karbuz A. Evaluation of clinical and laboratory characteristics of cases diagnosed with Hashimoto’s thyroiditis. Cerrahpaşa Med J. 2022;46(2):121-125.